The Basic Concept of Sufism Morals as the Initial Step in Purifying the Souls of Students - Khoirul Anwar (RAM PUBLISHER, 2025)
Sufism is a branch of Islamic knowledge that focuses on the spiritual dimension and purification of the soul (tazkiyah al-nafs). In Islamic boarding school education, Sufism plays a crucial role in shaping the character of students with noble morals. This article examines the basic concepts of Sufism morals and their relevance to the process of purifying the soul, encompassing values ​​such as sincerity, patience, asceticism, and contentment. This research used a descriptive qualitative literature study method. The results indicate that the stages of takhalli (emptying oneself of blameworthy traits), tahalli (filling oneself with praiseworthy traits), and tajalli (revealing Divine truth) are the main foundations in the process of purifying the soul. The implementation of these values ​​is not only relevant for the formation of insan kamil (perfect human beings) in Islamic boarding schools but also holds high relevance in the modern era for character education, self-control, mental health, and social ethics. Overall, Sufism morals are a transformative approach to building spiritual depth amidst the challenges of a fast-paced and materialistic life.